Business model innovation concepts, analysis, and cases - Afuah, Allan (Routledge, 2014)
Business Model Innovation explores the concepts, tools, and techniques that enable organizations to gain and/or maintain a competitive advantage in the face of technological innovation, globalization, and an increasingly knowledge-intensive economy. The book investigates how organizations can use innovations in business models to take advantage of entrepreneurial opportunities